Neonatal-perinatal medicine : diseases of the fetus and infant - Fanaroff, Avroy A; Martin, Richard J (Mosby, 2002)
This 2-volume \"bible\" of neonatology has been exhaustively updated to reflect all of the sweeping developments that have recently occurred in neonatal-perinatal medicine. Representing every relevant specialty, its 122 renowned contributors discuss everything from the latest discoveries in molecular biology, immunology, and genetics...through the newest techniques for ventilation and imaging...to the ethics of how viability is defined. In this comprehensively updated 5th Edition, 25% of the authors are brand new and all material incorporated evidence from the most recent clinical trials.
Keywords: Fetal Diseases; neonatologie; Neonatology; nemoci plodu; Pediatrics; pediatrie; perinatologie a neonatologie